Determination of five pesticides in kumquat: Dissipation behaviors, residues and their health risk assessment under field conditions - Zhixia Li (Elsevier, 2021)
The present study was carried out to profile the dissipation patterns and residues of five pesticides (triazophos, profenofos, chlorpyrifos, etoxazole and bifenthrin) on kumquat using QuEChERS method coupled with HPLC-MS/MS. The corresponding dietary health risks were also estimated. In the method validation, satisfactory results of good linearity (r2 ≥ 0.9956), sensitivity (limits of quantification ≤0.01 mg/kg), recoveries (71.0–95.7%) with relative standard deviations (0.70–9.4%) were obtained. The half-lives of the five pesticides in kumquat were 13.6–38.5 d under field conditions according to first-order kinetics. Based on the final residue experiment, dietary exposure risks of profenofos, chlorpyrifos, etoxazole and bifenthrin were all acceptably low, with RQc and RQa values of 0.00199–0.122 and 0.00145–0.200, respectively. However, exposure intake of triazophos posed unacceptable acute and chronic health risks for Chinese residents, especially for children with RQa and RQc up to 4.25 and 2.19. Forbidden use suggestion of triazophos and recommended MRLs of profenofos and bifenthrin were put forward in kumquat for safe production and consumption. This work was significant in providing guidance on appropriate application and MRL establishment of pesticides in kumquat.